How bees be - Boyle, Alison; Hambleton, Laura (London : Milet, 2003)
Little Bee thinks she can do whatever she wants, but when Queen Bee takes Little Bee under her wing, Little Bee learns it's not all fun and games to be an adult.
3.5
K-3
Keywords: Bees -- Fiction; Bees -- Fiction